On measuring the Hubble constant with X-ray reverberation mapping of active galactic nuclei. Issue 1 (18th October 2021) - Ingram, Adam; Mastroserio, Guglielmo; van der Klis, Michiel; Nathan, Edward; Connors, Riley; Dauser, Thomas; García, Javier A; Kara, Erin; König, Ole; Lucchini, Matteo; Wang, Jingyi
ABSTRACT: We show that X-ray reverberation mapping can be used to measure the distance to type 1 active galactic nuclei (AGNs). This is because X-ray photons originally emitted from the 'corona' close to the black hole irradiate the accretion disc and are reemitted with a characteristic 'reflection' spectrum that includes a prominent ∼6.4 keV iron emission line. The shape of the reflection spectrum depends on the irradiating flux, and the light-crossing delay between continuum photons observed directly from the corona and the reflected photons constrain the size of the disc. Simultaneously modelling the X-ray spectrum and the time delays between photons of different energies therefore constrains the intrinsic reflected luminosity, and the distance follows from the observed reflected flux. Alternatively, the distance can be measured from the X-ray spectrum alone if the black hole mass is known. We develop a new model of our reltrans X-ray reverberation mapping package, called rtdist, that has distance as a model parameter. We simulate a synthetic observation that we fit with our new model, and find that this technique applied to a sample of ∼25 AGNs can be used to measure the Hubble constant with a 3σ statistical uncertainty of 6 km s^-1 Mpc^-1 . Since the technique is completely independent of the traditional distance ladder and the cosmic microwave background radiation, it has the potential to address the current tension between them. We discuss sources of modelling uncertainty, and how they can be addressed in the near future.